(3eSFhdjI GdOhdI Yf JYhjV VMGjG GdchGQK (B/s - (3GdSjO, MeOj CHh GdfhQ,s 1967- ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdacQ GdLGeYj,s, 2016)
(3jJfGhd cJGH (B((3eSFhdjI GdOhdI Yf JYhjV VMGjG GdchGQK(B) (3hGdPj bGe HJCdjag (B((3MeOj CHh GdfhQ GdSjO(B) (3aj MhGdj (B(114) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdchGQK GdWHjYjI(B) (3eSJYQVG CHQR GdeMJhjGJ GdJGdjI (B: (3eHMK JegjOj (B: (3eaghe GdcGQKI, GdaUd GdChd (B: (3GdfXGe GdbGfhfj ddeSFhdjI Yf CVQGQ GdchGQK, GdaUd GdKGfj (B: (3eSFhdjI GdOhdI Yf CVQGQ GdchGQK aj GdTQjYI GdESdGejI hGdJTQjY GdeUQj(B.s
(3HHdjhLQGajI (B: (3UaMI (B103-112.s
Keywords: (3GdJYhjVGJs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdOhdIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3VMGjG GdchGQK s -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3eUQs